2021
DOI: 10.1002/lary.29780
|View full text |Cite
|
Sign up to set email alerts
|

In‐Office Superior Laryngeal Nerve Block for Paralaryngeal Pain and Odynophonia

Abstract: Objectives: Pain localized to the thyrohyoid region may be due to neuralgia of the superior laryngeal nerve (SLN), inflammation of the thyrohyoid complex, or a voice disorder. We present outcomes of treatment of paralaryngeal pain and odynophonia with SLN block.Study Design: Retrospective Review. Methods: A retrospective chart review of patients undergoing in-office SLN block for paralaryngeal pain between 2015 and 2018 at two tertiary care centers was conducted. Patient demographics, indications, and response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
4
1
Order By: Relevance
“…Several studies have utilized flexible laryngoscopy and videostroboscopy for the diagnosis and management of iVPG, including Devaney et al among many others 3,7,9,11,15–18 . This is consistent with diagnostic tests performed by respondents from our survey, as the most common modalities of diagnostic workup were videostroboscopy (88%) and flexible laryngoscopy (54%), as respondents reported that VPG is diagnosed clinically through visualization.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have utilized flexible laryngoscopy and videostroboscopy for the diagnosis and management of iVPG, including Devaney et al among many others 3,7,9,11,15–18 . This is consistent with diagnostic tests performed by respondents from our survey, as the most common modalities of diagnostic workup were videostroboscopy (88%) and flexible laryngoscopy (54%), as respondents reported that VPG is diagnosed clinically through visualization.…”
Section: Discussionsupporting
confidence: 86%
“…The recent publication by Tibbets et al supports use of the SLN block for paralaryngeal pain with 82% of patients reporting improvement. 14 This was higher than that observed in our study, with 59% reporting improvement. This can likely be attributed to the number of injections performed.…”
Section: Discussioncontrasting
confidence: 76%
“…As a first step, we recently demonstrated an improvement in paralaryngeal pain in 23 of 28 patients undergoing an average of 2.5 injections. 14 The objective of this multi-institutional study is to add to the body of literature on SLN block outcomes for treating neurogenic cough and to evaluate the effect of the SLN block on other ILS symptoms, including dysphonia related to laryngeal hypersensitivity, paralaryngeal pain, ILO, and isolated globus pharyngeus. We hypothesized that SLN block would provide symptomatic benefit across several ILS symptoms at short-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound guided superior laryngeal nerve block with clear location and less local soft tissue damage will not cause tracheal wall bleeding and hematoma formation, and the use of local anesthetics is limited. It can be performed with sufficient sedation and analgesia, making patients feel better [ 30 , 31 ]. In the current research reports, superior laryngeal nerve block is mainly used in the treatment of difficult airway, and the treatment of postoperative sore throat and neurogenic cough [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%